Studi Kematangan Batubara Formasi Warukin Berdasarkan Analisis Geokimia dan Reflectance Vitrinite di Barito Selatan, Kalimantan Tengah - Arica Nefia; Emanuel Grace Manek (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
The Warukin Formation is one of the principal coal-bearing units within the Barito Basin, where coal quality and maturity are strongly influenced by local geological conditions and thermal history. This study aims to determine the coal maturity level of the Warukin Formation in South Barito, Central Kalimantan, through the integration of geochemical analyses and vitrinite reflectance measurements. The methods employed include proximate and ultimate analyses, as well as vitrinite reflectance (Ro) measurements on four coal seams (Seams A, B, C, and D). Proximate analysis results on a dry mineral matter free (dmmf) basis indicate fixed carbon values ranging from 52.41–56.07%, volatile matter from 43.93–47.59%, and calorific values between 11,003.64–11,500.54 cal/g. These parameters consistently classify all seams as Subbituminous A coal rank according to ASTM standards. Vitrinite reflectance measurements show average Ro values ranging from 0.37% to 0.61%, generally corresponding to the Subbituminous rank, with localized increases up to High Volatile Bituminous C in Seam A. These findings indicate that the coal of the Warukin Formation in the study area exhibits low to moderate maturity, with localized variations in thermal maturity. The integration of geochemical data and vitrinite reflectance analysis proves effective in evaluating coal maturity and provides an important basis for assessing coal quality and utilization potential within the Barito Basin.